Pengaruh Return on Assets (ROA) dan Return on Equity (ROE) terhadap Harga Saham pada Perusahaan Agroindustri terdaftar di BEI Tahun 2021-2023 - Indy Ramadhani Putri Pountung; Tri Koko Apanugra; Rafika Chairani; Muhamad Hasbi; Akbar Anggisa (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to examine the effect of Return on Assets (ROA) and Return on Equity (ROE) on stock prices of agro-industrial companies listed on the Indonesia Stock Exchange (IDX) during the post-Covid-19 economic recovery period, specifically from 2021 to 2023. The research method used is a quantitative approach with a causal associative type. The data used are secondary data from annual financial statements and year-end stock prices. Data analysis was conducted using multiple linear regression with classical assumption tests to ensure model validity. The results indicate that ROA and ROE have both simultaneous and partial effects on stock prices. ROA demonstrates a stronger influence compared to ROE, suggesting that asset management efficiency is a key determinant of stock value in agro-industrial firms during the economic recovery period.